PROBLEMS IN EDUCATION DEVELOPMENT AND FACTORS AFFECTING IT - Xujakulova , Nigora Rustamovna; Poyonova , Aziza Nasriddin kizi (THE INNOVATION ECONOMY, 2025)
This article discusses the importance of developing the education sector and ensuring its quality, theories of developing and improving the quality of higher education, the main stages of the evolution of quality assurance in higher education, trends and problems, educational models, and considers multifaceted problems.